A Model for Determining Audit Fees with Emphasis on the Tone of Financial Reporting Based on Grounded Theory - Abdollahi, Taher; Jabbarzadeh Kangharloui, Saeed; Bahri Sales, Jamal; Pakmaram , Asgar (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The objective of this study is to develop a model for determining audit fees with an emphasis on the tone of financial reporting, using a grounded theory approach. Methodology: This research employs a qualitative methodology utilizing grounded theory based on the Strauss and Corbin approach. Data were collected through in-depth and semi-structured interviews with 12 participants, including auditors from firms, auditors from the Audit Organization, financial managers, and individuals with experience in contracting with auditors. The interviews were conducted between April and June 2021. Data analysis was performed using MAXQDA10 software, following open, axial, and selective coding procedures. Findings: The analysis identified 1,518 codes, leading to 38 subcategories and 14 main categories. The study found that client size, the complexity of operations, and the client’s budget significantly influence audit fees. It also highlighted that the tone of financial reports serves as a significant intervening factor, moderating audit fees. Specifically, a positive tone in financial reports is associated with lower audit fees, while a negative tone leads to higher fees. The findings suggest that firms with higher reputations and industry specialization command higher fees due to their perceived reliability and expertise. Conclusion: The study concludes that audit fee determination is a multifaceted phenomenon influenced by various factors, including client characteristics, firm reputation, industry specialization, and the tone of financial reporting. The tone of annual reports plays a critical role as an intervening variable, moderating audit fees either positively or negatively. The findings underscore the importance of considering qualitative factors, such as report tone, alongside traditional quantitative factors in audit fee determination. The study also provides recommendations for policymakers, audit firms, and corporate managers to enhance the fairness and rationality of audit fee structures.